Transfersome nanocarriers of green arabica coffee (Coffea arabica L.) bean extract: physicochemical characterization and in vitro antioxidant activity - Nur Adliani; Amelya Lukita; Yasinda Oktariza; Tantri Liris Nareswari (Pharmacy Reports, 2026)
Green Arabica coffee beans contain high concentrations of phenolic antioxidants, including chlorogenic acid and gallic acid, with demonstrated potential for topical skin protection. To enhance skin penetration and bioavailability of these active compounds, a transfersome delivery system was developed using ethanolic extract of green Arabica coffee beans from Aceh, Indonesia. Five formulations (F1–F5) were prepared by the thin-film hydration method with varying soybean lecithin:Tween 80 ratios (90:10 to 50:50), maintaining a total lipid mass of 500 mg and a fixed extract load of 50 mg. Physicochemical evaluation showed no significant differences in pH (5.41–5.46) across formulations, while viscosity of F1 was significantly higher than F2–F5 (p<0.05). Gallic acid content, determined by HPLC-UV, was highest in F4 at 45.370 mg/L. F4 also exhibited optimal particle characteristics (mean size 10.595 nm, zeta potential −30.5 mV, PDI < 0.3) and the strongest DPPH radical scavenging activity (IC50 = 2.652 ± 0.083 µg/mL). The 60:40 lecithin:Tween 80 ratio of F4 provided optimal bilayer flexibility without compromising vesicular integrity. These results support F4 as a promising topical antioxidant candidate; skin permeation and stability studies are required for further development.